Effective interventions of self-efficacy training in the reduction of test anxiety of student nurses in Ogbomosho north local government, Oyo state, Nigeria (2013)
"This study investigated the effectiveness of self-efficacy training in reducing test anxiety among student nurses. Fifty-one final year students of school of Nursing Ogbomoso, Oyo State, Nigeria were used for the study. The research adopted the 2x2 quasi experimental design and the major instruments used for the study were Sarason Text Anxiety Scale and the usual class achievement tests. The data were analyzed with the aid of Analysis of Variance (ANOVA). The findings indicate that the participants exposed to self-efficacy training showed a significant improvement in their academic performance than those in control group. Also, it was found that test anxiety when not properly managed has a significant negative effect on academic performance of students and that there are interactions effects between test anxiety and self-efficacy on the academic performance of the participant. It is recommended that self-efficacy strategies should be used for the treatment of test anxiety either for diminishing the crippling effects of test anxiety or to teach students how to utilize the anxiety to their advantage. "